REVIEW ON THE IMPLEMENTATION, PERCEPTIONS, AND OUTCOMES OF HUMANIZEDBIRTH IN LATIN AMERICA - Varillas Aldana, Alejandro Jesús (2025)
Humanized childbirth has been established as a woman-centered and rights-based model of care, promoted by the World Health Organization (WHO). This review analyzed the implementation, perceptions, and outcomes of the model in Latin America and the Caribbean, based on primary quantitative, qualitative, and mixed-methods studies published between 2021 and 2025. Included studies had clear operational definitions and provided data on women's experiences, practices aligned with WHO recommendations, and institutional performance. The studies reported positive perceptions from women, emphasizing empathy and respect in care; however, key limitations persisted, particularly regarding freedom of movement during labor, access to non- pharmacological pain management, and the presence of birth companions. Clinical benefits associated with the model were observed in health services, such as reduced medical interventions and earlier mother-infant contact, though barriers related to infrastructure, service overload, and time constraints were also noted. Qualitative findings revealed ongoing disrespectful institutional practices, lack of information, and rigid routines, but also highlighted the protective role of nursing staff and the relevance of culturally sensitive approaches. Overall, the results indicate significant regional progress, yet full implementation of the model remains incomplete. Greater standardization, continuous training, and cultural adaptation of services are required to ensure ethical, woman-centered care aligned with WHO frameworks.